Adenomatoid odontogenic tumor in the anterior mandible: a case report - Ferreira, Ketsia Rayssa Henriques; Meira, Clarina Louis Silva; Moraes, Josiclei de Castro; Daroz, Breno Gonçalvez; Souza, Lucas Lacerda de; Xavier, Thiago Brito (Journal of Oral Diagnosis, 2022)
Adenomatoid odontogenic tumor (AOT) is a rare, non-invasive, benign neoplasm of slow and progressive growth, originating from the odontogenic epithelium. The benign aspect of AOT predicts a more conservative approach through enucleation and curettage, with larger lesions being subjected to marsupialization prior to surgical treatment. This article aims to report a case of adenomatoid odontogenic tumor in the anterior mandible in a male patient who was treated with surgical marsupialization and posterior enucleation. Auxiliary therapeutic techniques can be used effectively to reduce the lesion, and accurate histological diagnosis is mandatory to avoid unnecessary aggressive surgery.